Fast Implementation of Transmit Beamforming for Colocated MIMO Radar - Sharma, Gollakota Venkata Krishna; Rajeswari, Konduri Raja (Společnost pro radioelektronické inženýrství, 2015)
Multiple-input Multiple-output (MIMO) radars benefit from spatial and waveform diversities to improve the performance potential. Phased array radars transmit scaled versions of a single waveform thereby limiting the transmit degrees of freedom to one. However MIMO radars transmit diverse waveforms from different transmit array elements thereby increasing the degrees of freedom to form flexible transmit beampatterns. The transmit beampattern of a colocated MIMO radar depends on the zero-lag correlation matrix of different transmit waveforms. Many solutions have been developed for designing the signal correlation matrix to achieve a desired transmit beampattern based on optimization algorithms in the literature. In this paper, a fast algorithm for designing the correlation matrix of the transmit waveforms is developed that allows the next generation radars to form flexible beampatterns in real-time. An efficient method for sidelobe control with negligible increase in mainlobe width is also presented.
Keywords: Multiple-input multiple-output radar; transmit beamforming; fast implementation; waveform diversity; zero-lag correlation matrix